THE EFFECTS OF WORD SQUARE MODEL ON SOCIAL SCIENCE LEARNING OUTCOMES OF 4th GRADE ELEMENTARY SCHOOL STUDENTS - Putri Amalia Ikhsani; Nurhasanah; Heri Hadi Saputra (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of the Word Square learning model on the social science learning outcomes of the fourth-grade students at SDN Gugus II Kecamatan Lingsar in the academic year 2020/2021. The type of this study was experimental research with a nonequivalent control group design, a type of quasi-experiment. The population in the study was students in grade IV SD Gugus II Kecamatan Lingsar, totaling 108 students, while the samples were grade IV students at SD Gugus II Kecamatan Lingsar, totaling 85 students. Data in this study were collected through documentation and questionnaires, while the instruments were social studies learning outcomes documents and Word Square model questionnaires. Then, the data were analyzed by the normality test, linearity test, and simple regression test to determine the effect of the Word Square model on learning outcomes. The results of the normality and linearity tests showed that the data were normally distributed and had a linear relationship. After going through the prerequisite test, a simple regression test was carried out, obtaining a sig. value of 0.000 < 0.05 or using a comparison of the value of tcount (3.974) > ttable (1.988). This means that Ha was accepted and H0 was rejected. Thus, the Word Square learning model significantly influenced the social science learning outcomes of the fourth-grade students of SDN Gugus II Kecamatan Lingsar in the academic year 2020/2021.